Information sharing, secrecy and trust among law enforcement and secret service institutions in the European Union. Issue 4 (4th July 2018) - Aden, Hartmut
Abstract: Transnational information sharing among security agencies in the European Union and beyond has grown considerably more important over the past decades. Centralised databases and numerous formal and informal networks now facilitate cooperation and information sharing. However, sharing intelligence may not only conflict with the protection of fundamental rights (data protection/privacy; presumption of innocence), but also with the organisational culture of institutions that are built upon secrecy. Police agencies often keep knowledge about individual cases and their strategies secret as long as possible. Intelligence services build their work and strategies upon secrecy even more. This paper analyses the variations of secrecy that can be observed for police agencies and secret services, and the relationship between information sharing among security agencies, secrecy, trust, transparency and accountability. In a normative perspective, the paper explores answers to the questions of how secret the work of security agencies should be in democratic rule of law systems and how accountability can be improved without making these institutions work less effectively.